2020
DOI: 10.21037/jtd-2020-abpd-001
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of ultrathin bronchoscopy in peripheral pulmonary lesions: a narrative review

Abstract: Flexible bronchoscopes are being continuously improved, and an ultrathin bronchoscope with a working channel that allows the use of a radial-type endobronchial ultrasound (EBUS) probe is now available. The ultrathin bronchoscope has good maneuverability for passing through the small bronchi and good accessibility to peripheral lung lesions. This utility is particularly enhanced when it is used with other imaging devices, such as EBUS and navigation devices. Multimodality bronchoscopy using an ultrathin broncho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 53 publications
0
31
1
Order By: Relevance
“…The use of a thin bronchoscope (4 mm outer diameter) and ultrathin bronchoscope (UTB; outer diameter less than 4 mm) might reduce the limitation of R-EBUS compared with using a conventional bronchoscope because they can reach more distal segmental bronchi leading to the lesion, which would result in a more precise direction alignment with the lesion and reducing the chance of displacement of the tip of the bronchoscope. [10][11][12][13] The present study found that the use of TB with R-EBUS and fluoroscopy resulted in a higher diagnostic yield in diagnosis of PPNs less than 30 mm compared to the previous study performed at our center (73.9% and 63.8%, respectively). 4 This was similar to the study of Tanner et al, which reported that the use of TB with R-EBUS could improve the diagnostic yield in the diagnosis of PPNs compared to the use of a conventional bronchoscope (49% and 37%, respectively; p = 0.110).…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…The use of a thin bronchoscope (4 mm outer diameter) and ultrathin bronchoscope (UTB; outer diameter less than 4 mm) might reduce the limitation of R-EBUS compared with using a conventional bronchoscope because they can reach more distal segmental bronchi leading to the lesion, which would result in a more precise direction alignment with the lesion and reducing the chance of displacement of the tip of the bronchoscope. [10][11][12][13] The present study found that the use of TB with R-EBUS and fluoroscopy resulted in a higher diagnostic yield in diagnosis of PPNs less than 30 mm compared to the previous study performed at our center (73.9% and 63.8%, respectively). 4 This was similar to the study of Tanner et al, which reported that the use of TB with R-EBUS could improve the diagnostic yield in the diagnosis of PPNs compared to the use of a conventional bronchoscope (49% and 37%, respectively; p = 0.110).…”
Section: Discussioncontrasting
confidence: 63%
“…10 The use of UTB combined with multimodality-guided techniques has been reported to provide a significantly higher diagnostic yield compared to the use of TB. [11][12][13] This advantage might be due to more distal bronchi being reached when using UTB. However, the diagnostic yields of UTB vary depending on the studies and guided methods, ranging from 40%-90%, with a yield of 24%-81% for lesions < 20 mm.…”
Section: Discussionmentioning
confidence: 99%
“…R‐EBUS has a high diagnostic yield (70.6%) and a very low complication rate for diagnosing PPLs 8 . Technological progress has led to the development of thinner bronchoscopes, which may increase the diagnostic yield for PPLs 29–31 . UTBs are designed to shorten the distance from the forceps to a lesion, which can increase the diagnostic yield.…”
Section: Discussionmentioning
confidence: 99%
“…Although the correct bronchial pathway is indicated by the navigation system, bronchoscopy may be unsuccessful when the bronchoscope or biopsy instrument cannot be advanced through the intended pathway. The development of reduced diameter bronchoscopes or catheter alternatives to bronchoscopes (e.g., robotic bronchoscopes and steerable extended working channels), which permit good accessibility through the small bronchus to the peripheral lung, has enhanced the diagnostic yield of bronchoscopy (14,(17)(18)(19)(20)(21). Recently, a 3.0 mm ultrathin bronchoscope with a 1.7 mm working channel was developed; this allows the use of rEBUS and has enabled the implementation of multimodal bronchoscopy (17)(18)(19).…”
mentioning
confidence: 99%
“…The development of reduced diameter bronchoscopes or catheter alternatives to bronchoscopes (e.g., robotic bronchoscopes and steerable extended working channels), which permit good accessibility through the small bronchus to the peripheral lung, has enhanced the diagnostic yield of bronchoscopy (14,(17)(18)(19)(20)(21). Recently, a 3.0 mm ultrathin bronchoscope with a 1.7 mm working channel was developed; this allows the use of rEBUS and has enabled the implementation of multimodal bronchoscopy (17)(18)(19). The fourth improvement was the development of instruments with better sampling ability and better maneuverability.…”
mentioning
confidence: 99%